PENGARUH MODEL QUANTUM TEACHING TERHADAP HASIL BELAJAR IPS SISWA SDN 050756 ALUR DUA - Syalsa Dwi Aprina; Ramadhan Lubis; Eka Yusnaldi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This study is motivated by the lack of student learning outcomes on the results of preliminary observations, it seems that the learning process in class IV SDN 050756 Alur Dua on Jalan Besitang Alur Dua Pasar, Alur Dua Village, Sei Lepan District, Langkat Regency on social studies learning has not been maximally implemented in learning through conventional learning models. Students lack motivation to learn as they should, therefore the learning process in the classroom is less than ideal so that it affects the learning outcomes of students. This research approach used by researchers is a quantitative approach and the type of research using quasi experiment (Pseudo Experiment). This data collection method uses, tests and documentation. The purpose of the study was to determine the results of whether there are differences in students who get the quantum teaching model and who do not get treatment. The results showed that there was a significant effect of using the Quantum Teaching model, this can be seen from the average value of the post test of each class. The social studies learning outcomes in the experimental class at the beginning of giving the pretest only get an average of 35.02 and the control class gets an average of 42.76. However, after getting treatment and being given a posttest the experimental class got an average result of 71.67 and the control class 58.19. From the research conducted, it was found that there was a significant influence on the social studies learning outcomes of fourth grade students of SDN 050756 Alur Dua. This can be seen based on the t test. The t test obtained t count t table is 2.801 2.048 then, Ho is rejected and Ha is accepted. Researchers who want to research with similar cases in the future, researchers recommend using subjects and others so that they can be used as comparative studies in improving the quality and quality of education.